Bacterial leaching of Pb -metallurgical wastes - P. Fecko; I. Janakova; E. Pertile; E. Kulova (Metalurgija, 2011)
The aim of this paper is verification of application of bacterial leaching and calcination to recover heavy metals from metallurgical wastes - matte from metallurgical plant Kovohute Pribram. For bacterial leaching a pure bacterial culture of Acidithiobacillus ferrooxidans was used. For a verification test an original sample of matte and matte from 2004 year were used. This paper further shows changes in the samples after bacterial leaching and after calcination. The paper results imply that the samples in question may be used as pigments.